2004
DOI: 10.1051/0004-6361:20040503
|View full text |Cite
|
Sign up to set email alerts
|

Transition region small-scale dynamics as seen by SUMER on SOHO

Abstract: Abstract. High spectral, spatial and temporal resolution UV observations of the quiet Sun transition region show a highly structured and dynamical environment where transient supersonic flows are commonly observed. Strongly non-Gaussian line profiles are the spectral signatures of these flows and are known in the literature as explosive events. In this paper we present a high spatial resolution (≈1 ) spectroheliogram of a 273 × 291 area of the quiet Sun acquired with SUMER/SOHO in the O  spectral line at λ10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 51 publications
8
79
0
Order By: Relevance
“…From the examples shown as EE1 and EE2, which are much smaller than the macrospicule, we estimate a value of a c = 7 km s −2 assuming v = ± 40 km s −1 and r as about the slit size of 0.3 . Similar values can be expected if we adopt the typical parameters mentioned by Teriaca et al (2004), namely a diameter of 2 and a velocity of 150 km s −1 . These violent motions could contribute to the solar wind acceleration (Pasachoff et al 1968).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From the examples shown as EE1 and EE2, which are much smaller than the macrospicule, we estimate a value of a c = 7 km s −2 assuming v = ± 40 km s −1 and r as about the slit size of 0.3 . Similar values can be expected if we adopt the typical parameters mentioned by Teriaca et al (2004), namely a diameter of 2 and a velocity of 150 km s −1 . These violent motions could contribute to the solar wind acceleration (Pasachoff et al 1968).…”
Section: Discussionsupporting
confidence: 84%
“…Typical EEs were found to be short-lived (60 s to 200 s), small-scale (1500 km to 2500 km), high-velocity (±50 km s −1 to ±150 km s −1 ) flows that occur very frequently, sometimes in bursts. Teriaca et al (2004) estimated an average size of 1800 km, a birth rate of 2500 s −1 , and 30 000 events at any one time on the entire Sun. In the classical view EEs are seen as bidirectional jets that are generated by a Petschek-type reconnection event (Innes et al 1997) high up in the TR with a collimated upflowing component -blueshifted in TR emissionand with a downflowing, redshifted component at some angle to the line-of-sight (LOS).…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion from this observation is that explosive events do not contribute significantly to the energy balance of the corona. The same conclusion was reached by Teriaca et al (2002bTeriaca et al ( , 2004.…”
Section: Explosive Eventssupporting
confidence: 78%
“…Further investigations with the help of the 17.1 nm and 19.5 nm passbands of TRACE and model calculations yielded consistent density and temperature values in coronal loops. Evidence was provided that hot (≈5 MK) and cold (≈2 × 10 5 K) fibrils together form a loop (Testa et al 2002). A disturbance observed by TRACE at one footpoint of a cold loop led to a strong red-shifted emission of N V at 123.8 nm emission at the other footpoint (Doyle et al 2006a).…”
Section: The Equatorial Corona Coronal Loops and The Slow Solar Windmentioning
confidence: 99%
“…Teriaca, Madjarska, and Doyle (2002) analysed spectral lines to determine whether or not transition region explosive events have coronal counterparts. Teriaca et al (2004) found cases where supersonic flows in small loops were associated with non-Gaussian line profiles. More recently, Madjarska, Doyle, and de Pontieu (2009) have demonstrated that explosive events and other transient phenomena may be the same processes, but observed in different ways.…”
Section: Introductionmentioning
confidence: 95%